Developing intercultural awareness through teacher-designed materials in the primary English classroom - Serrinha, Iara Rafaela Horta (2021)
The present research project focuses on investigating how students’ intercultural awareness can be developed in the primary English classroom through teacher-designed materials. As a consequence of globalisation, the world is ever more interconnected, and diversity is all around us. However, the topic of intercultural awareness has not been given proper attention in the primary English classroom in Portugal. Coursebooks tend to separate culture from language and resort to symbols and icons which only augment stereotypical ideas instead of attempting to show other realities and diversity. Learners should be given a deeper, varied and more realistic view of diversity between cultures and teacher-designed materials may be a useful resource to deepen learners’ intercultural awareness. I believe that the foreign language primary classroom is the ideal context to start laying the foundations for interculturally competent citizens and to raise inclusive and more tolerant human beings. This study took place in a 4th grade class in a primary school in Portugal. Three different topics were chosen to deepen students’ intercultural awareness using three different teacher-designed materials. To understand if students’ intercultural awareness was developed, questionnaires were administered before and after exposing students to the topics and materials. A teaching journal was also used to document students’ reactions throughout the project. The results show that teacher-designed materials can be effective to improve learners’ intercultural awareness as they became more knowledgeable, open, understanding, empathetic and curious. Learners also enjoyed the materials created by the teacher, and this proves that with the right motivation, the English classroom is an excellent place to open and augment students’ horizons.